Mechanism of alveolar bone destruction in periodontitis — Periodontal bacteria and inflammation. (November 2021) - Usui, Michihiko; Onizuka, Satoru; Sato, Tsuyoshi; Kokabu, Shoichiro; Ariyoshi, Wataru; Nakashima, Keisuke
Abstract: Periodontal disease is an inflammatory disease caused by periodontopathogenic bacteria, which eventually leads to bone tissue (alveolar bone) destruction as inflammation persists. Periodontal tissues have an immune system against the invasion of these bacteria, however, due to the persistent infection by periodontopathogenic bacteria, the host innate and acquired immunity is impaired, and tissue destruction, including bone tissue destruction, occurs. Osteoclasts are essential for bone destruction. Osteoclast progenitor cells derived from hematopoietic stem cells differentiate into osteoclasts. In addition, bone loss occurs when bone resorption by osteoclasts exceeds bone formation by osteoblasts. In inflammatory bone disease, inflammatory cytokines act on osteoblasts and receptor activator of nuclear factor-κB ligand (RANKL)-producing cells, resulting in osteoclast differentiation and activation. In addition to this mechanism, pathogenic factors of periodontal bacteria and mechanical stress activate osteoclasts and destruct alveolar bone in periodontitis. In this review, we focused on the mechanism of osteoclast activation in periodontitis and provide an overview based on the latest findings.